Nonlinear Predictive Control with Sliding Mode for Hypersonic Vehicle - Xiande Wu; Wenbin Bai; Yaen Xie; Qingnan Ma; Xiangshuai Song (International Journal of Aerospace Engineering)
Hypersonic vehicles are difficult to control due to their rapid time variation, dynamic nonlinearity, strong coupling, and model uncertainty. This paper proposes a new nonlinear predictive controller to solve the problem. An improved model predictive controller is used to improve the dynamic control performance of hypersonic vehicles by converting nonlinear dynamics into a state-dependent linear model. The sliding surface can significantly increase the speed of convergence. The radial basis function is used to reduce the influence of system uncertainty. The stability of the proposed controller is analyzed based on the Lyapunov approach. The comparison of simulation results verifies the excellent control performance of the proposed method both in convergence speed and antidisturbance ability.